Characterization of the Bacteriophage vB_VorS-PVo5 Infection on Vibrio ordalii: A Model for Phage-Bacteria Adsorption in Aquatic Environments - Echeverría-Vega, Alex; Morales-Vicencio, Pablo; Saez-Saavedra, Camila; Alvarez, María Alejandra; Gordillo, Felipe; Del-Valle, Rodrigo; Solís, Ma. Eugenia; Araya, Rubén (Frontiers in Microbiology, 2020)
We designed mathematical first-order difference equations to model the initial stage of the bacteriophage infection dynamics in aquatic environments under laboratory conditions. Our model only requires knowing the initial bacterial and bacteriophage numbers and to measure the average bacterial volume and velocity, to make predictions about the number of bacteriophages adsorbed on their host bacterial by time. The model was validated by experimental measurements in vitro, showing significant goodness of fit when compared the curves. This model was generated as an estimator for effectiveness of inoculation in phage therapy in aquaculture and opens to a wide range of potential applications.